Development of Financial Management and Financial Reports in Developing Creative Businesses: Pembinaan Manajemen Keuangan dan Laporan Keuangan dalam Mengembangkan Usaha Kreatif - Ika Fitriyani; Subhan Purwadinata; Nining Sudiharti (Cv. Utility Project Solution, 2022)
One of the efforts to provide students with an understanding as MSME business actors is to provide guidance on financial management. The purpose of this activity is that in addition to fostering student enthusiasm, it can provide knowledge and insight regarding MSME financial management and financial reports. That's why this activity predominantly leads to discussion and question and answer between students and presenters. In this activity the method applied is not only through discussion or question and answer but also through lectures. The benefits of this method are expected to provide convenience and understanding to students. This activity has run smoothly from start to finish. The implementation of this activity provides a spirit of enthusiasm for students in developing their business as independent young entrepreneurs. This activity has received a response from the Faculty, especially in the field of business unit managers to be willing to participate in developing student creative businesses. In the future, this activity is expected to continue to improve and continue optimally in providing experience to students in increasing entrepreneurial creativity.